Factors that Influence the Quality of the Tring by Pegadaian Application Service and its Relationship with Customer Satisfaction and Loyalty: A Case Study at the Purus Baru Syariah Pawnship Unit (UPS) in Padang City - Vanesya Amanda Yanedi Putri; Mike Yolanda (Scieclouds Publishing, 2026)
This study was conducted to analyze and identify the factors influencing the service quality of the Tring by Pegadaian app and their relationship with customer satisfaction and loyalty at the Purus Baru Sharia Pegadaian Unit in Padang. This study is a quantitative study. The population of this study consists of users of the Tring by Pegadaian app at the Purus Baru Sharia Pegadaian Unit in Padang, with a sample size of 100 respondents. In this study, analysis was performed using PLS-SEM with SmartPLS 4.0 software. The results of this study indicate that (1) Agility has a significant positive effect on Service Quality. (2) Assurance of Service has a significant positive effect on Service Quality. (3) Reliability has a significant positive effect on Service Quality. (4) Scalability has a significant positive effect on Service Quality. (5) Security has a significant positive effect on Service Quality. (6) Service Responsiveness has a significant positive effect on Service Quality. (7) Usability has a significant positive effect on Service Quality. (8) Service Quality has a significant positive effect on Customer Satisfaction. (9) Customer Satisfaction has a significant positive effect on Customer Loyalty. (10) Service Quality has a significant positive effect on Customer Loyalty.